Identification of Hard and Soft Tissue Anatomical Landmarks on Dental Intraoral Periapical Radiographic Images - Denise Mills; Vijay Parashar (Association of American Medical Colleges, 2015)
Abstract Introduction Dental and dental hygiene students are faced with the challenge of identifying anatomical structures on two-dimensional radiographic images. To better prepare novice learners for this difficult task, this module was created as an overview of normal anatomic structures of the maxillofacial region that are frequently imaged on periapical and bitewing images. Prerequisites for participation in the presentation include competency in head and neck anatomy as well as proficiency in radiographic techniques necessary to create periapical and bitewing images. Methods This module includes a PowerPoint presentation containing a series of radiographic images and corresponding overlaid photographic images providing an effective means for learning radiographic anatomy. Multiple-choice questions (answer key included for second portion of the presentation) in the presentation with identified responses make it a tool that is useful for lectures, small-group presentations, flipped-classroom activities, and student assessment utilizing audience response devices, written responses, or oral review. The session may be administered to small groups of approximately 12 students. Results This presentation has been presented to over 500 dental and dental hygiene students. Prior to the addition of overlaid photographic images to the presentation, the average score was 80%. Following the addition of overlaid photographs to the presentation, the average score exceeded 90%. Student surveys had many positive responses and they found the presentation to be extremely helpful with identifying landmarks. One student responded that the mini-session was most beneficial for teaching and learning. Another commented that the presentation clearly taught the concepts and ideas. The most insightful student response commented that the presentation helped explain the concepts well and got the students to interact with, and critically think about, the material. Discussion This presentation will help the learner connect prior knowledge of head and neck anatomy to structures observed in radiographic images. Concepts of radiolucency and radiopacity may be presented prior to the resource being used or in conjunction with the presentation. Ideas for future expansion of the presentation include adding panoramic images with superimposed photographs.